External debt, savings, and growth in Latin America : papers presented at a seminar sponsored by the International Monetary Fund and the Instituto Torcuato di Tella, held in Buenos Aires on October 13-16, 1986 - Martirena-Mantel, Ana María.; International Monetary Fund.; Instituto Torcuato Di Tella (Washington, D.C. ; Buenos Aires : The Fund ; El Instituto, 1987)
This book contains the proceedings of the seminars organized by the International Monetary Fund for Latin American countries held in Buenos Aires, Argentina on October 13-16, 1986.
Includes bibliographies.
usc 02/05/18
Loans
Keywords: Debts, External; Saving and investment; Economic policy; Latin America